Chasing Geographical and Social Mobility: The motivations of Nigerian madams to enter indentured relationships - Rizzotti, Milena (Anti-Trafficking Review, 2022)
This article draws from interviews with Nigerian women convicted of trafficking for sexual exploitation in Italy to challenge the simplistic public narrative of traffickers as ruthless foreign men who coerce naïve women into migration and sex work. Madams’ narratives shed light on a reality of trafficking where both traffickers and victims share similar desires to overcome constraints imposed on their geographical and social mobility through their migration to Europe. Therefore, the article calls for the inclusion of traffickers’ perspectives into the knowledge on human trafficking, which is mainly victim-centred and justifies the current anti-trafficking approach aimed at victims’ protection and traffickers’ punishment. In the research context, taking into consideration the perspectives of all trafficking actors involved suggests the need to rethink Nigerian women’s indentured migration to Europe through sex work (and policies around it) in terms of attempts to achieve geographical and social mobility rather than transnational criminal activities. Finally, the article provides recommendations on how to address these issues both within the current anti-trafficking policy domain and beyond it, by calling for more open borders.